Long-term survival of locally advanced stage III non-small cell lung cancer patients treated with chemoradiotherapy and perspectives for the treatment with immunotherapy - Vrankar, Martina (Radiology and oncology (Ljubljana), 2018)
Standard treatment for patients with inoperable locally advanced non-small cell lung cancer (NSCLC) is concurrent chemoradiotherapy (CCRT). Five-year overall survival rates range between 15 and 25%, while long term survival data are rarely reported. Patients and methods A total of 102 patients with stage III NSCLC treated between September 2005 and November 2010 with induction chemotherapy and CCRT were included in this long term survival analysis. All patients were tested for PD-L1 status and expression of PD-L1 was correlated with overall survival (OS), progression free survival (PFS) and toxicities. Results The median OS of all patients was 24.8 months (95% CI 18.7 to 31.0) with 10 year-survival rate of 11.2%. The median OS of patients with PD-L1 expression was 12.1 months (95% CI 0.1 to 26.2), while in patients with negative or unknown PD-L1 status was significantly longer, 25.2 months (95% CI 18.9 to 31.6), p = 0.005. The median PFS of all patients was 16.4 months (95% CI 13.0 to 19.9). PFS of patients with PD-L1 expression was 10.1 months (95% CI 0.1 to 20.4) and in patients with negative or unknown PD-L1 status was 17.9 months (95% CI 14.2 to 21.7), p = 0.003. Conclusions 10-year overall survival of stage III NSCLC patients after CCRT is 11.2%. PFS and OS differ with regard to PD-L1 status and are significantly shorter for patients with PD-L1 expression. New treatment with check-point inhibitors combined with RT therefore seems reasonable strategy to improve these results.
Keywords: imunoterapija; kemoradioterapija; lokalno napredovali rak; nedrobnocelični rak pljuč; pljuča; preživetje; rak (medicina); zdravljenje